1118 Are MND patients pre-morbidly fitter? Indirect evidence from hospital record-linkage. Issue 3 (9th February 2012) - Turner, M; Wotton, C; Talbot, K; Goldacre, M J
Abstract : Background: Case-control studies to identify risk factors for MND suffer from the intractable problem of recall bias, and have provided conflicting results. There is a persistent anecdotal observation that MND patients arise from a 'fitter' population. Such a physical profile might then be reflected in a reduced incidence of coronary heart disease (CHD) prior to the development of MND. Methods: A record-linkage study of a large national database of hospital admissions was undertaken. The ratio of the rate of MND in people without a record of CHD, to the rate in people with a record of CHD was calculated, factoring out premature death in the non-CHD and CHD cohorts. Similar analysis for Parkinson's disease (PD) and multiple sclerosis (MS) was undertaken. Results: Those without a record of CHD were at higher risk of ALS than those with CHD (rate ratio 1.14; 95% CI 1.05 to 1.22). The higher risk was not found for PD (0.95; 95% CI 0.93 to 0.98) or MS (0.95; 95% CI 0.88 to 1.04). Discussion: This study provides indirect support for the assertion that MND arises in a cardiovascularly fitter population. It has been proposed that greater physical activity might trigger MND, perhaps through oxidative stress. An alternative formulation might be that fitness in part reflects a distinct motor system architecture which, whilst associated with improved physical performance in youth, may be inherently vulnerable to the stochastic events of ageing.